2012
DOI: 10.1177/0363546512456974
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Arthroscopic Remplissage by High-Resolution Magnetic Resonance Imaging

Abstract: Our data suggest that there is evidence of tendon incorporation and fill into the Hill-Sachs defect following arthroscopic remplissage at 8 months and beyond. Although MRI findings did not correlate with the clinical findings, patients were satisfied with the procedure and demonstrated minimal loss of external rotation (average, 5.8°) at early follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
4
41
0
3
Order By: Relevance
“…Also, the size of the Hill Sachs deformity in all patients was measured on axial, coronal, and sagittal cuts where the largest value was recorded on each axis. This MRI measurement is similar to previously published work by Park et al [10].…”
Section: Methodssupporting
confidence: 91%
“…Also, the size of the Hill Sachs deformity in all patients was measured on axial, coronal, and sagittal cuts where the largest value was recorded on each axis. This MRI measurement is similar to previously published work by Park et al [10].…”
Section: Methodssupporting
confidence: 91%
“…In our study, recurrence of instability was noted in two patients. Park et al25) reported that there was evidence of tendon incorporation and filling into the Hill-Sachs defect following an arthroscopic remplissage, and patients were satisfied with the procedure and demonstrated minimal loss of external rotation (average, 5.8°) at an early follow-up. We also observed infraspinatus tendon was incorporated into the Hill-Sachs defect after the remplissage procedure and there was slight loss of external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,17 Even with small losses of only 2° to 8°, 3,4,19 the effects may have a greater impact in overhead athletes. 9 One explanation for external rotation loss may be due to overmedialization of suture placement.…”
Section: Discussionmentioning
confidence: 99%